Eruption of primary teeth in South Africans from one year of age - Hargreaves, J.A.; Cleaton-Jones, P.E.; Fatti, L.P.; Roberts, G.J.; Hargreaves, V (My University, 1997)
Erupted primary teeth were recorded in I 446 South African children from five communities. The data were grouped into 3-month age bands and subjected to Probit analysis. Eruption times were similar in boys and girls. Apart from children of Indian descent having significantly fewer incisor teeth erupted at one year compared to the four other groups, there were no significant differences in canine and molar eruption times among the children. This paper defines primary tooth eruption ages in South African children for anthropological, clinical and forensic use.
PK
Keywords: Tooth Eruption; Tooth, Deciduous; South Africa